Changes in von Willebrand factor level and von Willebrand activity with age in type 1 von Willebrand disease. (10th March 2015) - Rydz, N.; Grabell, J.; Lillicrap, D.; James, P. D.
Summary In a normal population, VWF plasma levels (VWF:Ag) and VWF activity (VWF:RCo) increase by approximately 0.17 and 0.15 IU mL−1 per decade, but the influence of age is unknown in patients with type 1 von Willebrand disease (VWD). In a retrospective cohort study, the medical records of 31 type 1 VWD patients over the age of 30, who had been followed for ≥5 years, were reviewed for baseline clinical data and previously performed VWF:Ag, VWF:RCo and factor VIII levels (FVIII:C). VWF multimer analysis was normal in 28/31 cases performed. Mean age at diagnosis was 33 (range 16–60 years), and duration of follow‐up ranged from 5 to 26 years (mean 11 years). Patients had 2–10 time points of VWD testing (mean of 5.2). The mean VWF:Ag, VWF:RCo and FVIII:C at time of diagnosis were 0.44 IU mL−1 0.34 IU mL−1 and 0.75 IU mL−1. At last follow‐up, the mean VWF:Ag, VWF:RCo and FVIII:C were significantly increased to 0.71 IU L−1, 0.56 IU mL−1 and 0.90 IU mL−1 (P ≤ 0.001, <0.001, and 0.0081 respectively). Here 18/31 patients had VWF:Ag, VWF:RCo and FVIII: C levels that increased into the normal range. The rate of change in VWF:Ag, VWF:RCo and FVIII was 0.30 IU mL−1 (0.21–0.39, CI 95%, P < 0.0001), 0.20 IU mL−1 per decade (0.13–0.27, CI 95%, P = 0.0001) and 0.20 IU mL−1 (0.11–0.29, CI 95%, P = 0.0011). Patients with type 1 VWD experience age‐related increases to VWF:Ag and VWF:RCo which can result in normalization of VWF levels. Further studies are required to determine if the bleeding phenotype resolves with the increases in VWF:Ag and VWF:RCo levels.